Patient Retention in Antiretroviral Therapy Programs; A Retrospective Cohort Study in a Triangular HIV Clinic: - Safari, Saeed; Khalatbari Limaki, Azadeh; Farhoudi, Behnam; Rasoolinejad, Mehrnaz; Rasoolinejad, Mehrnaz (Galen Medical Journal, 2017)
Background: High rate of adherence to antiretroviral therapy (ART) is critical for the optimized outcome. The present study aimed to determine the rate of retention in ART programs and its’ associated factors in a triangular clinic. Materials and Methods: The present retrospective cohort study was conducted on people living with HIV receiving care in a triangular clinic affiliated with Iranian research center for HIV/AIDS, Tehran, Iran, from 2003 to 2008. Baseline variables, duration of ART, and cause of treatment discontinuation were gathered using patients’ profile and analyzed by SPSS 21 and STATA 11. Results: Three hundred and seventeen cases with the mean age of 37.69 ± 10.63 (2–76) years were included (83.9% male). Treatment discontinuation had happened in 142 (45.2%) cases. Cause of treatment discontinuation was death in 20 (13.7%) cases and personal preference in 126 (86.3%) individuals. 6, 12, 18, 24, 36, and 60 months retention rates were 81.1%, 58.4%, 48.3%, 35.6%, 22.9%, and 6.3%, respectively. The results of multivariate logistic regression analysis showed a significant association between treatment retention and female sex (OR: 4.10; 95% CI: 1.59–10.56, P=0.003), addiction/drug use (OR: 0.39; 95% CI: 0.21– 0.77, P=0.007), and lamivudine+ zidovudine+ indinavir treatment regimen (OR: 0.63; 95% CI: 0.46 -0.87, P= 0.005). Conclusion: Based on the findings, male sex, addiction/drug use, and type of treatment regimen were among the most important risk factors for ART attrition in HIV-infected patients. [GMJ.2017;6(2):110-117]